2002
DOI: 10.3758/bf03195270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of theory-based feature correlations on typicality judgments

Abstract: It is generally agreed that our concepts are formed around clusters of correlated features (Rosch, 1978). For instance, having wings is more likely to occur with being able to fly and having feathers than with being able to swim and having gills. Thus, we give the name bird to creatures that have wings and feathers and are able to fly. Within these correlation clusters, there are specific feature correlations that are more important and explicit in our conceptual representations.In our bird concept, having win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…In a subsequent experiment, participants indicated the nature and direction of the relationship with a labeled arrow and numerically rated its strength. Because a greater number of participants provided labeled relations for explicitly related pairs and these relationships were judged to be stronger, Ahn et al (2002) concluded that explicitly related features were theory based. Finally, in a typicality rating experiment using artificial category exemplars, broken correlations influenced typicality ratings only when they involved explicit relations.…”
Section: Evidence For Causal Relationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a subsequent experiment, participants indicated the nature and direction of the relationship with a labeled arrow and numerically rated its strength. Because a greater number of participants provided labeled relations for explicitly related pairs and these relationships were judged to be stronger, Ahn et al (2002) concluded that explicitly related features were theory based. Finally, in a typicality rating experiment using artificial category exemplars, broken correlations influenced typicality ratings only when they involved explicit relations.…”
Section: Evidence For Causal Relationsmentioning
confidence: 99%
“…In this article, the term causal relations is used to refer to explicit beliefs about causal connections between features, in concert with definitions used previously (Ahn, Marsh, Luhmann, & Lee, 2002;Murphy & Wisniewski, 1989; although causal theories often refers to a wider range of causally based knowledge). A causal theory between two features explains how one feature, such as has a blade, is causally responsible for a second, such as used for cutting (Murphy & Medin, 1985).…”
Section: Causal Relations Between Featuresmentioning
confidence: 99%
See 3 more Smart Citations